Influence of Government Media Regulations on Audience Perception of News Credibility in Nigeria - Abdulrahman Ali Kolawole (Mdooter Journal of Communication and Digital Technologies)
Objectives: This study investigates the influence of government media regulations on audience perception of news credibility in Nigeria. Specifically, it examines how these regulations impact the diversity of viewpoints in news coverage and the perceived credibility of news sources.